Forecast Skill of the Arctic Sea Ice Outlook 2008–2022 - Edward Blanchard‐Wrigglesworth; Mitchell Bushuk; François Massonnet; Lawrence C. Hamilton; Cecilia M. Bitz; Walter N. Meier; Uma S. Bhatt (Geophysical Research Letters, 2023)
Abstract We assess the skill of forecasts of Arctic September sea ice in the Sea Ice Outlook over 2008–2022. The multi‐model median June initialized forecast of September sea ice extent (SIE) is slightly more skilled (RMSE = 0.48 million km2) than a damped anomaly forecast, but July and August initialized forecasts (RMSE = 0.52 and 0.36 million km2 respectively) do not beat this benchmark. The skill of individual dynamical and statistical SIE forecasts is lower than the multi‐model median forecast skill. Overall skill is lower than expected from retrospective forecasts. Several forecasts initialized in early September 2021 and 2022 imply physically improbable values. Spatial forecasts of sea ice concentration show multi‐model forecast skill and an improvement in individual forecast skill in recent years. Initial conditions show large spread in sea ice volume and a positive correlation between initialized sea ice volume and September SIE forecast. Summer weather has an impact on forecast error.